“Storie di sprawl”: la suburbanizzazione nel territorio bolognese - Manella, Gabriele; Rimondi, Tommaso (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2020)
“Sprawl cases”: the suburbanization in the Bologna region This paper moves from two research questions: what do people look for when they go living in the suburbs? What do they find? In the first part, the concepts of suburbanization and urban sprawl are considered, with attention to some socio-cultural aspects as well as the motivations that affect many downtown residents in “moving out”. In the second part, an analysis of statistical data on the Metropolitan City of Bologna is carried out to see some recent population movements between the capital city and the other municipalities as well as the commuting flows. The third part illustrate the results of some empirical studies in two Bologna suburbs: Casalecchio di Reno and Argelato. Namely, these studies consider the luxury residential complex Meridiana in Casalecchio di Reno and the census section n. 25 in Funo di Argelato. The study finds confirmation of several reasons that move people to the suburbs, some of which are “culturally strong” while other ones are “culturally weak”. The consolidation of suburbanization emerges too, but also the unsustainability of urban sprawl from all the points of view.